Evaluasi Pembelajaran Tematik Kelas Rendah di SDN Belendung Tengah 01 Kota Tangerang - Ina Magdalena; Puji Rahayu; Ria Aprilia; Wiwi Hilwiyah (RC-INSTITUT, 2020)
The purpose of this study was to find out the evaluation of Thematic learning of low class in knowing the evaluation of thematic learning in applying Thematic in SDN Belendung Tengah 01 and knowing how the teacher understood Thematic Middle Belendung 01 SDN 2013. The research method used in this study used the results of interviews between researchers and resource persons, with the determination of the resource persons in the Thematic section of SDN Belendung Tengah 01, according to the information we needed. Regarding how the evaluation of teachers in dealing with the 2013 thematic then the data is processed through a qualitative approach with descriptive methods. Conclusions from the results of research on teacher issues in applying Thematic 2013 and evaluations used by teachers in dealing with Thematic 2013 applications at Belendung Tengah Elementary School 01.